An Eco-friendly Route to Synthesis of Quinolines - Mishra, A. D. (Journal of Nepal Chemical Society, 2012)
Some 2-hydroxy-4-methyl-6- substituted quinoline derivatives have been synthesized in an environmentally benign method from easily available 4-substituted anilines and ?-Ketoesters, under ordinary conditions. The reactions were catalyzed by aluminium chloride to afford excellent amount of the products. The usage of hazardous acids, bases and solvents have been avoided in different steps of the reactions completely, which has made this synthetic method one step advance to the existing methods. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6670 J. Nepal Chem. Soc., Vol. 27, 2011 115-119